Response of Plant Rhizosphere Microenvironment to Water Management in Soil- and Substrate-Based Controlled Environment Agriculture (CEA) Systems: A Review - Tan, Bo; Li, Yihan; Liu, Tiegang; Tan, Xiao; He, Yuxin; You, Xueji; Leong, Kah Hon; Liu, Chao; Li, Longguo (Frontiers in Plant Science, 2021)
As natural agro-ecology deteriorates, controlled environment agriculture (CEA) systems become a backup support to cope with future resource consumption and potential food crisis. Compared with natural agro-ecology, most of the environmental parameters of the CEA system rely on manual management. Such a system is dependent and fragile, and is prone to degradation, including harmful bacteria proliferation and productivity decline. Proper water management is significant for constructing a stabilized rhizosphere microenvironment. It has been proven that water is an efficient tool, which can change the availability of nutrients, plant physiological processes and microbial communities within. However, for CEA issues, relevant research is lacking at present. The article reviews the interactive mechanism of water management with rhizosphere microenvironment from perspectives of physicochemical properties, physiological processes, and microbiology in CEA systems. We presented a synthesis of relevant researches on water-root-microbes interplay, aimed to provide with detailed references to conceptualization, research, diagnosis and troubleshooting for CEA systems, and attempted to give suggestions on construction of artificial high-tech agricultural ecology.